A REVIEW ON SILICONE RUBBER/ MONTMORILLO-NITE NANOCOMPOSITES (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
Silicone rubber (SIR) is superior to natural rubbers due to having special features like high chemical stability, heat, abrasion and ozone resistance. Global markets show huge attention to produce and use silicone rubber in many applications such as aerospace, automobile, construction, electric insulators and medical industries. Although silicone rubber is hugely utilized in high voltage insulators, it shows low properties such as mechanical properties. Therefore, fillers are added to silicone rubber in order to reducing cost and improving the surface hydrophobicity, thermal and/or electrical conductivity, thermal and/or electric insulation and mechanical properties. This paper reviews on structure, types, general properties, manufacturing methods, applications of SIR, fillers and silicone rubber nanocomposites. It is focused on the popular micro/nanoparticles for dielectric applications. Organic montmorillonite (OMMT) represents one of the most important fillers that are used for dielectric applications. OMMT is added to SIR to improve the cost and electric and thermal insulation and mechanical properties. Tensile properties of SIR/OMMT nanocomposites increased with increasing the content of OMMT. SIR/OMMT nanocomposites with smaller OMMT size showed the highest compression strength and the lowest tear strength. SIR/OMMT Nanocomposites with high content of OMMT displayed greater thermal stabilities, flame retardant properties, dielectric permittivity and dielectric loss.